Timing of onset of cognitive decline: results from Whitehall II prospective cohort study. - Singh-Manoux, A; Kivimaki, M; Glymour, M; Elbaz, A; Berr, C; Ebmeier, K; Ferrie, J; Dugravot, A (2012)
OBJECTIVES: To estimate 10 year decline in cognitive function from longitudinal data in a middle aged cohort and to examine whether age cohorts can be compared with cross sectional data to infer the effect of age on cognitive decline. DESIGN: Prospective cohort study. At study inception in 1985-8, there were 10,308 participants, representing a recruitment rate of 73%. SETTING: Civil service departments in London, United Kingdom. PARTICIPANTS: 5198 men and 2192 women, aged 45-70 at the beginning of cognitive testing in 1997-9. MAIN OUTCOME MEASURE: Tests of memory, reasoning, vocabulary, and phonemic and semantic fluency, assessed three times over 10 years. RESULTS: All cognitive scores, except vocabulary, declined in all five age categories (age 45-49, 50-54, 55-59, 60-64, and 65-70 at baseline), with evidence of faster decline in older people. In men, the 10 year decline, shown as change/range of test × 100, in reasoning was -3.6% (95% confidence interval -4.1% to -3.0%) in those aged 45-49 at baseline and -9.6% (-10.6% to -8.6%) in those aged 65-70. In women, the corresponding decline was -3.6% (-4.6% to -2.7%) and -7.4% (-9.1% to -5.7%). Comparisons of longitudinal and cross sectional effects of age suggest that the latter overestimate decline in women because of cohort differences in education. For example, in women aged 45-49 the longitudinal analysis showed reasoning to have declined by -3.6% (-4.5% to -2.8%) but the cross sectional effects suggested a decline of -11.4% (-14.0% to -8.9%). CONCLUSIONS: Cognitive decline is already evident in middle age (age 45-49).